The Effect of Using a Manual Accounting System on the Accuracy of Financial Statements in Small and Medium Enterprises (SMEs) Medan Marelan - Syahlina, Maya (International Journal of Advanced Research, 2025)
Good financial management is a key factor in the sustainability of small and medium enterprises (SMEs). One important aspect of financial management is the accounting system used. This study seeks to examine the impact of employing a manual accounting system on the precision of financial reporting for SMEs in Medan Marelan. The research methodology employed is a quantitative approach, including data collection approaches via surveys and interviews with small and medium-sized enterprise (SME) stakeholders. This research offers an overview of the efficacy of manual accounting methods in documenting financial transactions and generating precise financial reports. This paper examines the challenges encountered by SMEs in implementing manual accounting systems and proposes alternate alternatives to enhance the accuracy of financial statements. This study's results aim to elucidate the significance of accounting systems in enhancing company performance for SMEs, academics, and other stakeholders.